SISTEM MONITORING GARDU INDUK PLN DENGAN PENERAPAN INTERNET OF THINGS - Ahmad, Ahmad; T, Husain; Herlinda, Herlinda; Kasmawaru, Kasmawaru (University of Muhammadiyah Tangerang, 2025)
The area surrounding power transformers at substations must remain free from wild animals, as their presence can disrupt the flow of electricity, potentially causing equipment damage and reducing the reliability of the electrical system. This study aims to design and implement an automated monitoring system based on the Internet of Things (IoT) to detect the presence of animals near high-voltage equipment (150 kV) at the Tallasa substation. The proposed system integrates Passive Infrared (PIR) and ultrasonic sensors with an ESP32-CAM microcontroller to detect animal movement in real time. Detection data is transmitted to an IoT platform via WiFi or cellular networks, and real-time alerts are sent through the Telegram application to enable a prompt response by personnel. Test results indicate that the system demonstrates high accuracy in detecting animals under both daylight and low-light conditions. Furthermore, real-time notifications enhance monitoring responsiveness and enable early intervention to prevent potential disruptions. With its reliable and consistent performance, the system presents an effective and sustainable solution for maintaining the operational integrity of transformer protection systems and perimeter barriers.